The impact of closed perforation zones and damaged sections on flow dynamics and pressure behaviors of horizontal wells - Al Rbeawi, Dr. Salam (Journal of Petroleum Research and Studies, 2017)
Horizontal wells with multiple completion parts have become a common completion technique in the oil and gas industry. Sand and asphalt production problems, damaged zones and water cresting or gas coning are the main reasons for using this technique to sustain or improve oil and gas recovery. However, using such completion technique introduces negative effects on pressure behavior of horizontal wells. This paper introduces new mathematical models for horizontal well containing several closed completed sections acting in finite and infinite reservoirs. These models can be used to evaluate the impact of the completion techniques on both pressure behaviors and flow regimes either in the vicinity of wellbore or at the outer boundary of reservoirs. They can be used also to investigate the change in productivity index that would result due to the usage of certain type of completion technique. In this research, the completed sections (cemented or isolated parts) and the places where packers are installed are considered as no-flow sections. These sections are expected to increase pressure drop required for flowing reservoir fluid toward wellbore. They are also expected to change flow regimes mainly in the vicinity of wellbore. Several models have been developed and solved in this study for different completion techniques, wellbore conditions and reservoir configuration. It has been found that the great impact of completion techniques is observed on flow regimes that commonly develop in the drainage area close to wellbore. This impact shows similar trends to the skin factor. Several new flow regimes have been observed, one of them has been developed due to the existence of closed completed sections which is intermediate or second radial flow regime. This flow regime can be found for some cases of long wellbore having multi-short perforated sections. The study will introduce the mathematical models for known and newly developed flow regimes for horizontal well including the completion technique.